Benefits of an NHS trust collaborating with the wound care industry. (1st March 2021) - Collier, Mark
Abstract : The principle of collaborative working was widely promoted by the World Health Organisation (WHO) in 2010 when they wrote 'that professionals who actively bring the skills of different individuals together, with the aim of clearly addressing the health-care needs of patients and the community, will strengthen the health system and lead to enhanced clinical and health related outcomes'. As a result of this, the development of a multidisciplinary team approach to the management of patients with wounds was actively promoted by various International organisations, such as the European Wound Management Association (EWMA) in 2014, however this article illustrates an example of how a collaborative working protocol has been incorporated within Tissue Viability and wound care environments within an NHS Trust for the past two decades.